'Dog-beating stick': General Zhang Aiping's contribution to the modernisation of China's nuclear force and strategy since 1977. Issue 4 (2nd October 2018) - Liu, Lei
Abstract: Since the Reform and Opening-up in the late 1970s, the second generation of the Chinese Communist Party (CCP) leadership, led by Deng Xiaoping, worked towards a breakthrough in the development of strategic nuclear weapons and employment policy. By the middle 1980s, the Chinese military had successfully developed China's first generation of intercontinental ballistic missiles (ICBM), submarine-launched ballistic missiles (SLBM), and communication satellites, which provided China with an elementary and limited second-strike capability. These technological advances were complemented by advances in Chinese nuclear strategy as well. Despite retaining the basic principle of no-first-use of nuclear weapons, the Chinese military leaders, such as Deng and General Zhang Aiping, gradually accepted the concept of nuclear deterrence. Meanwhile, they put forward China's own concepts, including 'da gou gun' ('dog-beating stick'), 'huan shou zhi li' ('the power to strike back'), 'xia hu ren' ('bluff'), and 'di you wo you, di yong wo yong' ('we have whatever the enemy has; we use whatever the enemy uses'). All of these new strategic weapons and concepts, which came from the 1980s, have been playing a key role in ensuring that China enjoyed limited nuclear deterrent since the late 1980s. Zhang devoted most of his attention to these achievements.